The Effect of Various Comparison of the Proportions of Seaweed (Eucheuma spinosum) and Gelatin on the Characteristics of Roselle Jelly Candy (Hibiscus sabdariffa L.) - Hikam Fuadi; Ida Agustini Saidi (Universitas Muhammadiyah Sidoarjo, 2021)
Rosela flower (H. sabdariffa L.) is one of the plants that has many health benefits, which contain Vitamin C, Vitamin A, essential proteins, and 18 types of amino acids that aim to strengthen the body's immune system, treat diabetes, inhibit cancer cells and many more properties of this plant. Gelling agent commonly used to make jelly candy is gelatin, but in the application sometimes gelatin even makes the texture of jelly candy becomes very hard if the added concentration is not appropriate, besides the price of special gelatin food ( food grade) is still relatively expensive compared to other hydrocolloid materials. That's why it takes another gel shaper that can improve the quality of the texture of jelly candy and suppress the use of gelatin, one of which can be used seaweed (E. spinosum). The objective of this research was to find out the effect of various proportions of seaweed (E. spinosum) and gelatin on the characteristics of roselle jelly candy (H. sabdariffa L.). The method used is non-parametric statistical tests (Friedman test) with 10 levels of treatment and performed three times the test on each treatment. The treatment that will be done is a comparison of various proportions of seaweed: gelatin, namely PI (0: 8); P2 (0: 10); P3 (25:8); P4 (25:10); P5 (30:8); P6 (30:10); P7 (35:0); P8 (35:8); P9 (40:0) and P10 (40:8). The results showed there was a very noticeable difference in all the comparative treatment of seaweed and gelatin proportions against all test parameters. The best organoleptic test results showed color organoleptic test scores of 3.00 (neutral), organoleptic textures of 3.37 (neutral-like), organoleptic flavors of 3.40 (neutral-like) and organoleptic aromas of 3.00 (neutral).